2020
DOI: 10.1097/j.pbj.0000000000000083
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve fenestrations: a review

Abstract: Background: Aortic valve fenestrations (AVFs) seem to be relatively common; however, their impact in human heart disease is not entirely clear. Methods: A review was carried out to assess all scientific literature on human patients related to AVFs, as described in the published literature. The search was conducted on 2 different databases, Medline (PubMed), and ISI Web of Knowledge. Results: Fifty-five repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Yet, a recent report by Yang et al suggested that aortic valve fenestrations may account for 3.1% of moderately severe and severe aortic valve insufficiencies (Yang et al, 2019). Moreover, many case reports have described fenestration-associated aortic valve regurgitations (Jodati et al, 2014;Symbas et al, 1969;Zhu et al, 2020). Especially, the in the patient in which the presence of multiple and large fenestrations exist, these F I G U R E 2 Functional endoscopic view of the aortic valve with multiple fenestrations in leaflets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, a recent report by Yang et al suggested that aortic valve fenestrations may account for 3.1% of moderately severe and severe aortic valve insufficiencies (Yang et al, 2019). Moreover, many case reports have described fenestration-associated aortic valve regurgitations (Jodati et al, 2014;Symbas et al, 1969;Zhu et al, 2020). Especially, the in the patient in which the presence of multiple and large fenestrations exist, these F I G U R E 2 Functional endoscopic view of the aortic valve with multiple fenestrations in leaflets.…”
Section: Discussionmentioning
confidence: 99%
“…It is still not entirely clear, whether fenestrations in aortic valve leaflets may play significant role in the pathophysiologies of various aortic valve diseases (Zhu et al, 2020). Nevertheless, the presence of the aortic leaflet fenestrations has been linked to hemodynamically significant aortic valve regurgitations (Yang et al, 2013;Zhu et al, 2020); especially, if large and centrally located apertures in the leaflet structure are present which may be responsible for a leaky valve (Jodati et al, 2014). The presence of the fenestrated regions within the valvular tissues may lead to the significant losses of leaflet stiffnesses and therefore be associated with prolapses (Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fenestration of aortic valve is a common condition that rarely cause aortic incompetency. In one study, it accounts for 3.1% of AR mechanisms among patients [ 9 ].Usually, fenestrations are located in the commissures, and their frequency is higher in men, BAV, and valves with myxomatous degeneration. Regurgitation can occur in large fenestration or, in rare cases, in spontaneous rupture of fenestration [ 10 ].…”
Section: Discussionmentioning
confidence: 99%